Transformation Of Science Learning Through Augmented Reality: Its Impact on Critical Thinking Abilities of Elementary School Students - Hasna Muthi Luthfiyah; Dede Margo Irianto; Yusuf Tri Herlambang; Diki Somantri; Tono Sutanto; Yadi Suryadi (CV. Ksatria Siliwangi, 2025)
Low critical thinking skills among elementary school students regarding abstract concepts, such as Earth and Moon movements, present a significant challenge in implementing the Merdeka Curriculum, which emphasizes critical reasoning. This study aims to analyze the influence of Assemblr EDU-based Augmented Reality (AR) on enhancing the critical thinking skills of sixth-grade students. A quasi-experimental method with a non-equivalent pre-test post-test control group design was utilized, involving 56 students divided into experimental (n=28) and control (n=28) groups. Data collection instruments included critical thinking tests and observation sheets, followed by statistical analysis using Wilcoxon, Mann-Whitney, and N-Gain Score tests. The findings revealed a substantial disparity in outcomes; the experimental group achieved a mean post-test score of 91.25, significantly higher than the control group's 57.86. Furthermore, the N-Gain analysis showed that Assemblr EDU reached an effectiveness level of 84.7% (High category), whereas the control group only attained 27.9% (Low category). These results demonstrate that 3D visualization through AR effectively bridges the cognitive transition from the concrete operational to the abstract thinking stages. Consequently, this study provides a strong recommendation for educational practitioners to integrate AR-based media into Science (IPAS) instruction to foster students' analytical, inferential, and evaluative competencies optimally at the primary education level.